2012
DOI: 10.5751/es-05057-170410
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Two Payment Schemes for Watershed Services from China and Vietnam: the Interface of Government Control and PES Theory

Abstract: ABSTRACT. China and Vietnam have developed some of the most ambitious payments for ecosystem services (PES) initiatives for watershed conservation and forest management. These include the Sloping Land Conversion Programme in China and pilot projects designed to implement Decision 380 and the subsequent national PES law in Vietnam. This study reviews how these two government-driven initiatives are achieving their environment and development objectives in terms of their institutional arrangements, implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 44 publications
(69 reference statements)
0
50
0
5
Order By: Relevance
“…Insisting on neoliberal frameworks as principal drivers of PES in Vietnam obscures that PES has become a non-conditional, Keynesian-type social welfare program of cash transfers that households understand as reconfirming their historic relationship to the state and the importance of rural upland spaces to national development. Other cases of alterations to the rationales and practices of PES governance leading to the failure of neoliberal logics include a series of large-scale PES programs in China, which shares much of Vietnam's state socialist history (Yin et al, 2013;Kolinjivadi and Sunderland, 2012), the Working for Water program of the Republic of South Africa, labelled as PES for reasons of political expediency but structured as a public works and employment generation program (Buch and Dixon, 2009;Hough and Prozesky, 2013), and the Bolsa Floresta program of Amazonas State in Brazil modelled after a federal poverty reduction and social development program, Bolsa Familia, providing a suite of subsidies and assistance for local public works, strengthening of governance, capacity building, and other social programs (Bakkegaard and Wunder, 2014).…”
Section: Evidence Of the Monster? Empirical Examples Of The Contestatmentioning
confidence: 99%
“…Insisting on neoliberal frameworks as principal drivers of PES in Vietnam obscures that PES has become a non-conditional, Keynesian-type social welfare program of cash transfers that households understand as reconfirming their historic relationship to the state and the importance of rural upland spaces to national development. Other cases of alterations to the rationales and practices of PES governance leading to the failure of neoliberal logics include a series of large-scale PES programs in China, which shares much of Vietnam's state socialist history (Yin et al, 2013;Kolinjivadi and Sunderland, 2012), the Working for Water program of the Republic of South Africa, labelled as PES for reasons of political expediency but structured as a public works and employment generation program (Buch and Dixon, 2009;Hough and Prozesky, 2013), and the Bolsa Floresta program of Amazonas State in Brazil modelled after a federal poverty reduction and social development program, Bolsa Familia, providing a suite of subsidies and assistance for local public works, strengthening of governance, capacity building, and other social programs (Bakkegaard and Wunder, 2014).…”
Section: Evidence Of the Monster? Empirical Examples Of The Contestatmentioning
confidence: 99%
“…Based on studies in northeast China, Wang and Maclaren [69] concluded that the targeting process was generally inefficient because productivity and environmental heterogeneity were ignored. There were many critics of the inefficient top-down implementation approach [24,35] associated with quota systems [46,70], and most blamed the local government, which preferred the easier-to-implement method of simplifying the plots-based selection [45,71].…”
Section: Effective Implementationmentioning
confidence: 99%
“…Non-cash incentives, such as clear land tenure and technical assistance, should be given more attention in consideration of local budget constraints . Technical and agricultural extension support for land-use transitioning and empowering community-based institutions and individuals through micro credits and loans are also suggested (Kolinjivadi & Sunderland, 2012). Combining PES and reduce emission from deforestation and degradation (REDD) mechanisms with support for climate-change adaptation would help to reduce fee collection and channelling of finances, as well as the high transaction costs.…”
Section: Incentive-based Approachmentioning
confidence: 99%
“…The project undertook different actions aimed at achieving integrated watershed management, which included enhanced community water access (springs, dams, tanks, pipes and boreholes) and river basin management planning and monitoring (MKEPP Report, 2007). The project also distributed tree seedlings to farmers, rehabilitated degraded indigenous forests, established plantation forests and planted trees on hilltops and along riverbanks (Ministry of Water and Irrigation, Kenya, 2006 (Hoang, Do, Pham, van Noordwijk, & Minang, 2013;Kolinjivadi & Sunderland, 2012).…”
Section: Landscape Approachmentioning
confidence: 99%